Vremena goda . Vremena goda . Four Seasons . Времена года - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. A classical music concert: the Latvian State Philharmonic Orchestra plays Antonio Vivaldi's "Four Seasons." Концерт классической музыки. Камерный оркестр Латвийской государственной филармонии играет произведения Антонио Вивальди "Времена года".